2019
DOI: 10.1108/ijoes-10-2018-0144
|View full text |Cite
|
Sign up to set email alerts
|

Workplace spirituality, psychological well-being and mediating role of subjective stress

Abstract: Purpose The purpose of this study is to assess the impact of spirituality on subjective stress and psychological well-being (PWB). Additionally, the study also examines the mediating role of stress in the spirituality – well-being relationship. Design/methodology/approach The study is quantitative in nature. Data were collected from 322 secondary school teachers using a structured questionnaire. Partial least squares based structural equation modelling was used to analyse the data. Findings Results indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 65 publications
4
35
0
Order By: Relevance
“…This definition is in accordance with the definition by the World Health Organisation, which described occupational or job stress as "the response people may have when presented with work demands and pressures that are not matched to their knowledge and abilities, and which challenge their ability to cope" (World Health Organization, 2020). This definition clearly demonstrates that stress occurs when employees' capabilities do not meet what is ultimately expected of them (Mahipalan & Sheena, 2019). More definitions of stress from previous studies are presented in Table 1.…”
Section: Review Of Literature Work Stress As a Predictormentioning
confidence: 84%
See 1 more Smart Citation
“…This definition is in accordance with the definition by the World Health Organisation, which described occupational or job stress as "the response people may have when presented with work demands and pressures that are not matched to their knowledge and abilities, and which challenge their ability to cope" (World Health Organization, 2020). This definition clearly demonstrates that stress occurs when employees' capabilities do not meet what is ultimately expected of them (Mahipalan & Sheena, 2019). More definitions of stress from previous studies are presented in Table 1.…”
Section: Review Of Literature Work Stress As a Predictormentioning
confidence: 84%
“…A distressingly high number of mental health issues among the working-age group have recently been observed. Wide studies focus on work stress and job satisfaction; despite the importance of these variables, the focus is now shifting to employees' emotional and mental health (Mahipalan & Sheena, 2019). The mental health issue is primarily caused by work stress resulting in reduced employees' productivity, tense relationships, and loss of mental calmness (Sharma & Srivastava, 2020).…”
Section: Review Of Literature Work Stress As a Predictormentioning
confidence: 99%
“…Afsar and Badir (2017) showed that employees' workplace spirituality was positively related to self and IB. Spirituality could be an important element in managing the work attitude of Generation Y workers creatively (Mahipalan & Sheena, 2019). As a result, the following hypothesis could be formulated: H1: Spiritual leadership has a positive significant effect on innovative behaviour.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%
“…These results imply that an employee's experience of spirituality in the workplace has an impact on his perception, which in turn helps engage him to display IB more often. Mahipalan and Sheena (2019) showed that there was a significant relationship between spirituality and work and organisational engagement. Based on the findings, it is reasonable to assume that spirituality could be an important element in managing the work attitudes of creative Generation Y workers.…”
Section: The Effect Of Employee Engagement On Innovative Behaviourmentioning
confidence: 99%
“…However, the empirical studies examining the impact of spirituality in the workplace in managing occupational stress are sparse. Also, the studies identifying the linkages between WPS and OS have majorly examined academicians, students, nursing and other professionals (Bell et al, 2012; Chand & Koul, 2012; Csiernik & Adams, 2012; Daniel, 2015; Mahipalan & Suresh, 2019; Sharafi et al, 2014; Tischler et al, 2002). The present study explores the linkages between WPS and OS in a stress-prone occupation like policing, which is imperative for maintaining peace and order in any society.…”
Section: Introductionmentioning
confidence: 99%